2019
DOI: 10.1037/per0000347
|View full text |Cite
|
Sign up to set email alerts
|

Pathological narcissism and psychosocial functioning.

Abstract: Pathological narcissism involves maladaptive efforts to regulate the self and is conceptualized by 2 key features: narcissistic grandiosity and narcissistic vulnerability. Prior research has found that narcissism is associated with poorer functioning over the long term, especially interpersonal functioning. Despite this, the specific contributions of grandiosity and vulnerability to different domains of functioning remain understudied. In particular, there has been scant literature investigating pathological n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 45 publications
2
22
0
Order By: Relevance
“…It might be that individuals high on narcissistic grandiosity have a higher integrated identity because they are more likely to maintain their self-esteem by employing overt strategies, such as self-enhancement and devaluation of others [ 30 ]. The result may fit into previous studies showing that individuals with grandiose narcissistic traits are better adjusted compared to individuals with vulnerable narcissistic traits [ 39 , 40 , 45 , 76 – 78 ]. For example, Ng et al [ 76 ] found that grandiose narcissism predicted higher life satisfaction and lower perceived stress, whereas vulnerable narcissism showed the opposite pattern.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…It might be that individuals high on narcissistic grandiosity have a higher integrated identity because they are more likely to maintain their self-esteem by employing overt strategies, such as self-enhancement and devaluation of others [ 30 ]. The result may fit into previous studies showing that individuals with grandiose narcissistic traits are better adjusted compared to individuals with vulnerable narcissistic traits [ 39 , 40 , 45 , 76 – 78 ]. For example, Ng et al [ 76 ] found that grandiose narcissism predicted higher life satisfaction and lower perceived stress, whereas vulnerable narcissism showed the opposite pattern.…”
Section: Discussionsupporting
confidence: 89%
“…Second, since identity diffusion is one of the key features of a narcissistic personality disorder [ 41 , 42 ], we hypothesized that both grandiose and vulnerable narcissism would be directly and negatively associated with identity integration (path 3 and path 4, respectively). Nonetheless, this link might be expected to be weaker for grandiose narcissism, as grandiose narcissism has been documented to be associated with a narrower range of poor identity functioning and better life satisfaction compared to vulnerable narcissism [e.g., 39 , 40 ]. Furthermore, it has been shown that identity diffusion can lead to deviant behavior and a range of maladaptive outcomes such as poor impulse control [ 48 – 51 ].…”
Section: The Present Studymentioning
confidence: 99%
See 2 more Smart Citations
“…Other studies in adolescence, however, have related grandiose narcissism traits to psychopathology [ 94 , 95 ]. It is thus unclear whether grandiose narcissism being unrelated to shame and insecure attachment in this study is an adaptive form of narcissism [ 66 , 96 ] or whether the relation between grandiose narcissism and shame and attachment experiences might be challenging to capture with self-report measures [ 31 ]. Research using measures of implicit self-esteem and implicit shame have found a relation with grandiose narcissism [ 34 , 97 , 98 ].…”
Section: Discussionmentioning
confidence: 99%